The key pillars of psychosocial disability: a European perspective on challenges and solutions - Martinelli, Alessandra (Frontiers in Psychiatry, 2025)
Psychosocial disabilities refer to a range of mental health conditions that significantly impact an individual’s ability to function in daily life and participate fully in society. Across Europe, individuals with these conditions face systemic barriers, including inadequate support services, stigma, and limited healthcare access. This perspective article examines these challenges through the lens of Maslow’s hierarchy of needs and Saraceno’s community psychiatry framework. By analyzing identified key pillars of psychosocial disability - housing, social inclusion, employment, healthcare access, service organization, and stigma – this article underscores the necessity of targeted interventions to promote dignity, autonomy, and recovery for individuals with psychosocial disabilities across Europe. Stable housing is foundational for recovery, social integration, and employment. Social inclusion and meaningful employment are essential for psychological well-being, though stigma and discrimination remain a major obstacle. Employment programs are crucial for fostering social reintegration. Healthcare access, already fragmented, can be obstacolated by stigma in healthcare settings as an additional barrier. Positive organizational culture in mental health services, emphasizing co-production and shared decision-making, is vital for recovery and healthcare access. This article highlights how key pillars of psychosocial disability are strongly interrelated, with each significantly influencing the others. The reciprocal impact among these elements demonstrates that improvements or setbacks in one area inevitably affect the others, creating either a reinforcing cycle of support or a compounding negative effect. Coordinated efforts and comprehensive strategies are essential to integrating these pillars and overcoming barriers to psychosocial disability across Europe.